2011
DOI: 10.1007/s10753-011-9358-9
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Stimulants Promote the Expression of a Promiscuous G Protein-Coupled Receptor, mFPR2, in Microvascular Endothelial Cells

Abstract: Human formylpeptide receptor 2 (FPR2) and its mouse homologue mFPR2 belong to the G protein-coupled, seven-transmembrane receptor superfamily. Both FPR2 and mFPR2 recognize a variety of exogenous and host-derived chemotactic peptides associated with proinflammatory conditions. Since endothelial cells actively participate in inflammation, we investigated whether microvascular endothelial cells express mFPR2 and its regulation by proinflammatory factors. We found that resting primary mouse microvascular endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…We found that SCAP expressed a relatively low level of ALX/FPR2 in comparison with PBMC, however, this expression was upregulated by pro-inflammatory factors (TNF-α and LPS). These results are in line with other studies using microglial or endothelial cells 16 , 27 . Although no mechanistic studies have been performed at this point, we may hypothesize that ALX/FPR2 is upregulated through c-Jun N-Terminal protein kinase and transcription factor NF-κB signaling pathways as discussed in other studies 16 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that SCAP expressed a relatively low level of ALX/FPR2 in comparison with PBMC, however, this expression was upregulated by pro-inflammatory factors (TNF-α and LPS). These results are in line with other studies using microglial or endothelial cells 16 , 27 . Although no mechanistic studies have been performed at this point, we may hypothesize that ALX/FPR2 is upregulated through c-Jun N-Terminal protein kinase and transcription factor NF-κB signaling pathways as discussed in other studies 16 .…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we identified for the first time that SCAP express the lipoxin receptor ALX/FPR2. The expression of ALX/FPR2 is upregulated by a variety of inflammatory stimulants such as TNF-α, interferon-γ as well as ligands for TLR-2, 3, 4, 7 and 9 in different cell types 15 , 16 . Although the effect was apparently weaker in comparison with microglial cells or microvascular endothelial cells, we demonstrated that important inflammatory mediators of pulpal and periapical diseases such as TNF-α and LPS upregulated ALX/FPR2 expression in SCAP.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of FPRs is highest in sentinel innate cells with phagocytic or chemotactic activity such as neutrophils [13] , [14] , monocytes [13] , [15] , macrophages [15] , [16] and dendritic cells [15] , [17] . However, FPR are also expressed in non-phagocytic and “immobile” sentinel cells such as mucosal epithelial cells [18] , [19] , endothelial cells [20] [22] and glia [23] [25] . In these cells, FPRs exert a genuine “sentinel role” by sensing pathogens present in the microenvironment as well as by favouring repair upon damage and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In the present report it is shown that FPR2/ALX receptor is constitutively expressed in VSMC and that LPS increased its expression in both the cell line A7r5 and mouse aorta. So far, LPS has been shown to increase FPR2/ALX expression in microglia (Cui et al, 2002) and in microvascular endothelial cells (Mou et al, 2012).…”
Section: Discussionmentioning
confidence: 99%